Drag Reduction Technology of Ultra-long Directional Drilling and Its Application - WANG Xian, JIANG Lei, LI Quanxin, XU Chao (Meikuang Anquan, 2020)
In view of the problems such as high resistance, low efficiency and limited drilling depth during the sliding directional drilling under the condition of deep hole, this paper studies and forms the drag reduction technology of sliding drilling, including hydraulic pressure drilling technology and positive and negative twist drilling technology. This technology has been applied to complete a 3 353 m ultra-long directional drilling along coal seam in Baode Coal Mine. Analysis of drilling parameters shows that the technology has obvious drag reduction effect of sliding drilling, which has great significance to improve the drilling capacity, drilling efficiency and drilling trajectory control accuracy of ultra-long directional drilling in coal mine.